2020
DOI: 10.3389/fpls.2020.00092
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Root Nitrogen Uptake Between Tropical Lowland Rainforests and Oil Palm Plantations

Abstract: Conversion of lowland tropical rainforests to intensely fertilized agricultural land-use systems such as oil palm (Elaeis guineensis) plantations leads to changes in nitrogen (N) cycling. Although soil microbial-driven N dynamics has been largely studied, the role of the plant as a major component in N uptake has rarely been considered. We address this gap by comparing the root N contents and uptake in lowland rainforests with that in oil palm plantations on Sumatra, Indonesia. To this aim, we applied 15 N-lab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 63 publications
1
9
0
Order By: Relevance
“…Another study revealed that when was evaluated the N application and N uptake e ciency in oil palm crop versus a tropical forest, the root N content was onethird higher in the tropical forest compared with oil palm plantations. Nevertheless, the absorption e ciency was similar in both systems (Edy et al, 2020). Both in our results and in those discussed previously suggest that the decrease in the content of the elements in the soil is due to the need for absorption or use required by the oil palm for the formation of clusters of fresh fruits (Edy et al, 2020;Manorama et al, 2021).…”
Section: Diameter Fresh and Dry Weight Of The Rootssupporting
confidence: 78%
See 1 more Smart Citation
“…Another study revealed that when was evaluated the N application and N uptake e ciency in oil palm crop versus a tropical forest, the root N content was onethird higher in the tropical forest compared with oil palm plantations. Nevertheless, the absorption e ciency was similar in both systems (Edy et al, 2020). Both in our results and in those discussed previously suggest that the decrease in the content of the elements in the soil is due to the need for absorption or use required by the oil palm for the formation of clusters of fresh fruits (Edy et al, 2020;Manorama et al, 2021).…”
Section: Diameter Fresh and Dry Weight Of The Rootssupporting
confidence: 78%
“…Nevertheless, the absorption e ciency was similar in both systems (Edy et al, 2020). Both in our results and in those discussed previously suggest that the decrease in the content of the elements in the soil is due to the need for absorption or use required by the oil palm for the formation of clusters of fresh fruits (Edy et al, 2020;Manorama et al, 2021). In this line, the present experiment showed that higher values of the elements K, Mg, Cu, S, Mn, and Zn are present in 3-year-old plots and the pastures compared to 15-year-old adult plants.…”
Section: Diameter Fresh and Dry Weight Of The Rootsmentioning
confidence: 85%
“…Therefore, P and N availability are likely limiting factors for soil microorganisms; consequently, tight associations between soil nutrients and community composition occur frequently [27,30,97,98]. However, the shifts in fungal communities are unrelated to root N uptake, which is similar in rainforests to that in oil palm plantations [99].…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that our measured soil N cycling rates represented soil conditions beyond the short-term pulse effects of N-fertilizer application, which generally caused elevated mineral N concentrations for up to six weeks following fertilization (Hassler et al 2017). Thus, the generally comparable soil N cycling rates between the fertilized palm circle and the unfertilized inter-row suggest that excess N from pulse N fertilizer application may have been taken up by the palms (Edy et al 2020), lost via gaseous emissions (Hassler et al 2017), or moved down in the soil profile and eventually leached (Formaglio et al 2020). The low gross N mineralization in the palm circle illustrated the inherently low N-supplying capacity of the soil in this intensively managed area, and illustrated its dependence on chemical fertilizer inputs to maintain palm productivity.…”
Section: Controls On Soil N Cycle and Comparison With Smallholder Plantations And Forestsmentioning
confidence: 92%